Strategi Content Creator dalam Membangun Brand Awareness Tiktok @Bogornative - Azizah, Auliya; Pranata, Rici Tri Harpin (Petanda: Jurnal Ilmu Komunikasi dan Humaniora, 2025)
The purpose of this study is to analyze content creators' strategies in building brand awareness through the TikTok platform, with a case study of the @bogornative account. Brand awareness is defined as the audience's ability to recognize, remember, and associate a brand with a particular product category (Kotler Keller, 2016; Aaker David, 2018). This study uses a descriptive qualitative approach with purposive sampling techniques, involving content creators, creative teams, and social media managers as informants. Data were collected through in-depth interviews, observation, active participation, and literature review. The results show that Bogor Native applies Petty's (1997) five stages of the creative process, namely inspiration, distillation, perspiration, evaluation, and incubation, to produce relevant and interesting content. The content is organized into six pillars: tourism, culinary, culture, events, vibes, and shopping recommendations, with persuasive storytelling, attractive visuals, and intense audience interaction. The success of this strategy is measured by the number of views, which reflects the audience's awareness of the brand. This strategy allows the audience to recognize the brand, remember it, place it at the top of their minds, while strengthening the image of the city of Bogor and increasing the brand's reach on TikTok.